Diagnostic role of serum prolactin level in different kinds of seizure and seizure-like episode in children: A hospital-based study - Priyanka Kumari,; Sudipto Paul,; Moshihur Rahaman Sk,; Laha, Sumanta; Saikat Mondal,; Aditya Kayal, (Asian Journal of Medical Sciences, 2024)
Background: Serum prolactin level has been previously used in distinguishing epileptic seizure from non-epileptic seizure, as prolactin level usually rises following an epileptic seizure in children. Aims and Objectives: We conducted this study to determine the role of serum prolactin as a surrogate marker of seizure disorder and whether serum prolactin level varies between different types of seizure, febrile seizure, and seizure mimics. Materials and Methods: This cross-sectional comparative study was conducted for 1 year among 113 children between 6 months and 16 years of age of either sex. They were divided into 3 groups (1) epileptic seizure, (2) febrile seizure, and (3) seizure mimics. The blood sample was collected within 1 h of the occurrence of seizure for estimation of serum prolactin level. Each child was investigated and treated according to the protocol. Results: Mean post-ictal prolactin level was found significantly higher in epileptic seizure (29.94±7.97 ng/mL) compared to febrile seizure (10.21±0.94 ng/mL), and seizure mimics (8.73±0.67 ng/mL). Among group 1, serum prolactin levels significantly elevated in children with generalized tonic-clonic seizure (GTCS) (34.18±2.76 ng/mL) and complex partial seizure (CPS) (31.38±1.59 ng/mL) compared to simple partial seizure (SPS) (14.36±2.33 ng/mL). Post-ictal serum prolactin levels remain elevated for a longer duration in GTCS (54.26±5.19 min) and CPS (45.19±1.73 min) compared to children with SPS (26.76±2.33 min). Conclusion: Estimation of serum prolactin level within 1 h after a seizure can be used for screening purposes to distinguish between epileptic and non-epileptic seizures. A high prolactin level is suggestive of GTCS or CPS whereas a low level is indicative of SPS, febrile convulsion, or seizure mimics with a prolactin cutoff taken 24 ng/mL in our study.